Implementation of intergovernmental relations frame work act in the delivery of services : the case of the Greater Giyani Municipality, Limpopo Province - Maluleke, Pule Thomas (University of Limpopo, 2017)
The local sphere of government is the crucible of services delivery in South Africa, however since the first local government election, various local government authorities have been plagued by service delivery. In order to improve such delivery at local level, various legal and policy instruments has been designed, including the enactment of Intergovernmental Relations Framework Act 13 of 2005 (IGRFA). Despite the promulgation the IGRFA to formalise cooperation and collaboration between State departments and the local government authorities, municipalities are still grappling with inefficient and ineffective implementation of service delivery programmes. These failures have resulted in incidents of violent protest by members of local communities against local municipalities across all provinces. The study examines the implementation of intergovernmental relations (IGR) and Intergovernmental Relation Frame Work Act, and the effect thereof on the efficiency and effectiveness of service delivery through the prism of Greater Giyani Municipality. The study has adopted the qualitative research methods to determine the extent of IGR and IGRFA implementation amongst and between state institutions. The study also made application of quantitative study to determine the efficiency and effectiveness of service delivery undertaken by state institutions within Greater Giyani Municipality. The study found that there are various challenges which impede the implementation of IGR and IGRFA amongst the state institutions, and that such impediments result in ineffective and inefficient rendering of services within the Greater Giyani Municipality. The study further highlights the actions which need to be taken in order circumvent factors which impacts on the implementation of IGRA and IGRFA amongst State institutions. The study makes recommendations which may be adopted by officials of both national and provincial departments and municipalities in order to improve the implementation of IGR and IGRFA to enhance the efficiency of the execution of service delivery programmes. The study has also developed a framework which can be used to enforce the implementation of IGR and IGRFA for the augmentation of service delivery within local municipalities.
Thesis (MPA.) -- University of Limpopo, 2017
Keywords: Local municipality; Service delivery; Intergovernmental relations; Greater Giyani Municipality; Municipal services; Intergovernmental fiscal relations - South Africa; Municipal services -- Law and legislation -- South Africa